Labour market marginalisation in young refugees and their majority peers in Denmark and Sweden: The role of common mental disorders and secondary school completion - de Montgomery, Christopher Jamil; Norredam, Marie; Krasnik, Allan; Petersen, Jørgen Holm; Björkenstam, Emma; Berg, Lisa; Hjern, Anders; Sijbrandij, Marit; Klimek, Peter; Mittendorfer-Rutz, Ellenor (PLOS ONE, 2022)
Background Due to the circumstances of their early lives, young refugees are at risk of experiencing adverse labour market and health outcomes. The post-settlement environment is thought to play a decisive role in determining how this vulnerability plays out. This study compared trends in labour market marginalisation in young refugees and their majority peers during early adulthood in two national contexts, Denmark and Sweden, and explored the mediating role of common mental disorders and secondary school completions. Methods Using registry data, 13,390/45,687 refugees were included in Denmark/Sweden and 1:5 matched to majority peers. Inequalities in labour market marginalisation were investigated during 2012–2015 in each country using linear probability models and mediation analysis. Country trends were standardised to account for differences in observed population characteristics. Results The risk of marginalisation was 2.1–2.3 times higher among young refugees compared with their majority peers, but the risk decreased with age in Sweden and increased in Denmark for refugees. Birth-cohort differences drove the increase in Denmark, while trends were consistent across birth-cohorts in Sweden. Differences in population characteristics did not contribute to country differences. Common mental disorders did not mediate the inequality in either country, but secondary school completions did (77–85% of associations eliminated). Conclusions The findings document both the vulnerability of young refugees to labour market marginalisation and the variability in this vulnerability across post-settlement contexts. While the contrast in policy climates in Denmark and Sweden sharpened over time, the risk of marginalisation appeared more similar in younger cohorts, pointing to the importance of factors other than national immigration and integration policies. Institutional efforts to assist young refugees through secondary education are likely to have long-lasting consequences for their socio-economic trajectories.